Analysis of Elements Business Model in Coffee Shop - Erika Putri; Sri Astuti; Camelia Safitri (Economic Education Analysis Journal, 2023)
The study aims is to determine the elements of the canvas business model with three focuses, there are customer segment, value proposition and key resources at The Buddy House Coffee & Eatery. The research method used is descriptive qualitative. The data collection technique used is passive participant observation, semi-structured interviews and documentation. The data analysis technique used is data reduction, data display and conclusions and data validation using triangulation. The informants in this study were selected purposive sampling and snowball sampling as many as 3 people there are 1 Head Barista and 2 consumers. The results showed that the targeted customer segments are the middle social class, and the majority of consumer come from outside the area where the coffee shop was located. Meanwhile, for the value proposition element, of the 11 indicators, there are 2 indicators that have not been implemented optimally, there are newness and accessbility. In the key resource element, intellectual indicators must be maximized in terms of creating copyright on products made by The Buddy House Coffee & Eatery.